An Agrippan source; a study in Indo-Parthian history - Mukherjee, Bratindra Nath, 1932- (Pilgrim Publishers, 1969)
On the Arsacids, Indo-Parthian rulers, according to Marcus Vipsanius Agrippa, ca. 64-ca. 12 B.C.